ALGORITMOS GENÉTICOS NA FORMAÇÃO DE GRUPOS PARA APRENDIZAGEM COOPERATIVA APOIADA POR COMPUTADOR - Lima, Mark Renato Campos (2006)
This work presents a boarding based on genetic algorithms for the resolution of the groups formation problem for the computer supported cooperative learning. In this boarding the problem is defined as a optimization task in which if it intends to optimize the quality of the groups formed for the application of the cooperative model of teach-learning used in computerized environments. This quality is subjects the pedagogical factors that can be established by the pedagogical model of the learning environment and is taken in question for the considered method of formation. It is evaluated use of the boarding proposal applying it in the environment of NetClass teach-learning, developed for the Federal University of the Maranhão.